Probabilistic-based geomechanical assessment of maximum operating pressure for an underground gas storage reservoir, NW China. (September 2022) - Wang, Bin; Li, Daoqing; Xu, Bin; Zhang, Yi; Zhang, Fengshou; Wang, Quan; Yang, Baohong
Abstract: One of the most cost-effective ways to increase deliverability and working gas capacity in underground gas storage (UGS) reservoirs is to operate the gas storage at higher pressure (increased delta pressure). Maximum operating pressure (MOP) for a gas storage reservoir depends on several geomechanical factors, including in-situ stresses, stresses induced by local and global pressure changes in the storage reservoir, and the stabilities of the caprock and faults. PetroChina's Hutubi (HTB) gas storage site is located in the west gate of China's west–east gas pipeline project. Multiple major faults intersect the gas storage reservoir and caprock, which pose safety concerns for increasing the gas storage pressure. The typical practice in an HTB storage site has been to operate gas storage pressures at levels equal to the original reservoir pressure because of concerns related to caprock integrity and fault stability. To investigate the possibilities of increasing the gas storage pressure, a comprehensive geomechanical study has been conducted. By utilizing the data from rock mechanics laboratory testing, in-situ stress measurements, 3D field-specific geomechanical models, and coupled reservoir-geomechanical simulations, this paper presents probabilistic risk assessment of fault slippage in response to injection-related increases in pore pressure. Uncertainties of relevant geomechanical parameters, such as the frictional strengths of faults, orientation, and magnitudes of in-situ stresses, have been incorporated through Monte Carlo simulations. The authors find that: (1) fault slippage is the controlling factor which determines the limit of MOP at a HTB gas storage site; (2) increasing the gas storage pressure by 12.5% above the initial reservoir pressure (34.5 MPa) leads to approximately 0.6% probability of fault instability that could provide a leakage pathway. Thus, from a geomechanical perspective, operating the storage pressure at initial reservoir pressure at a HTB gas storage field is an overly conservative approach that leads to under-utilization of the existing storage capability. This paper provides the first integrative geomechanical study for increasing MOP for large underground gas storage reservoir in China. The methodology as well as comprehensive data repository are potential sources for future geomechanical studies on similar underground gas storage projects. Highlights: Coupled reservoir-geomechanics study for increasing the maximum operating pressure of large underground gas storage reservoir in China. Carry out probabilistic-based geomechanical modeling of fault slippage and caprock integrity. Operating the storage pressure at initial reservoir pressure is an overly conservative approach.